Implementasi Metode Overall Equipment Effectiveness Dan Six Big Losses Pada Cutting Machine - Irma Nurmala Dewi; Arta Rusidarma Putra; Hadi Kurniawanto; Ombi Romli; Dedy Khaerudin (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Every company is obliged to carry out efficiency strategies in every business process in order to continue to exist in today's increasingly fierce competition. This research aims to determine the magnitude of the OEE value and the dominant factors from the six big losses analysis which is used as a proposal for improvements to the cutting machine at PT ABC. The method used is Availability Ratio, Performance Ratio and Rate of Product Quality as basic elements of Overall Equipment Effectiveness and Six Big Losses and analyzed using a fishbone diagram. Calculation results for the period September 2023 to February 2024 obtained an OEE value of 82.58% with the largest contributor to losses being the idling and minor stoppages and Reduce Speed ​​factors. To overcome this, it is necessary to increase skills in identifying and repairing machines, implementing clear standard operating procedures, operator skills in conveying information about machine damage, as well as standard material for parts used by machines.